Generation of cardiomyocytes by atrioventricular node cells in long-term cultures - Kiuchi, Shigeki (Biochem Biophys Rep, 2021)
Turnover of cardiac pacemaker cells may occur during the lifetime of the body, and we recently raised the hypothesis that specialized cardiac cells have in common the potential to generate cardiomyocytes from fibroblasts. To examine this hypothesis, we analyzed the ability of atrioventricular node cells (AVNCs) to generate functional cardiomyocytes in long-term culture. AVNCs were isolated from adult guinea pig hearts and cultured for up to three weeks. Under phase-contrast microscopic observation over time, it was found that within a week, a number of fibroblasts gathered around the AVNCs and formed cell clusters, and thereafter the cell clusters started to beat spontaneously. The nascent cell clusters expanded their area gradually by three weeks in culture and expressed specific cardiac genes and proteins. Maturation of newly formed cardiomyocytes seems to be slow in cultures of AVNCs compared with those of sinoatrial node cells. Stimulation of muscarinic receptors with acetylcholine induced a beating rate decrease which was blocked by atropine, and activation of adenylate cyclase activity with forskolin increased the beat rate, while stimulation of beta adrenoceptors by isoproterenol had no effect. These results indicate that AVNCs form a cluster of cells with properties of functional cardiomyocytes and provide evidence to support the hypothesis.